(untitled) (Global Journal of Management and Business Research, 2013)
In a time where instant gratification is just simply considered as a norm cellphone is just an item that teen cannot go out without it is becoming a major problem in today s generation At this age in which we need to read good books in which we need to write proper letters on actual paper at this time youngsters are getting into sending and receiving sms The youth is not just social but it s becoming anti-social than ever before They just prefer to text each other but not bother to interact face to face due to cheap sms packages that just cost them a rupee in their way Text messaging has become preferred mode of communication for majority of youngsters Widespread availability of cheap unlimited text message plans has made the service as preferred mode of communication for youngsters and its excessive use is leading to health problems among them Aim of our research is to check the addiction of SMS in youth which leads to the health problems We distributed the questionnaires among the students of the universities We analyzed our data with the help of SPSS program The results of the research indicate that perceived usefulness and information on the addiction of sms and causes health problem in youth Everyone should take some steps to control these problems in order to live a healthy life style